Islam, Atheism and Anti-natalism: A critical analysis (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2021)
The fact that every one of us in this life has to face difficulties, pain, sadness cannot be denied. Quran and Hadith also accept the presence of evil and calamities in this world. There comes the question in our mind that how is the evil present in this world although the world is created by Allah (S.W.T), and He is the merciful and controls everything in the universe. If somehow, the evil was present Allah (S.W.T) could have ended it, but we see that the reality is different. The existence of evil has been used by people as a justification for not believing in God since ages. In today’s world we see people who believe in Anti-natalism and consider life as an evil and in order to save ourselves from the evil they suggest that humans should not procreate. This article has been written after studying the arguments of people who do not believe in God and are the followers of Anti-natalism. The study concludes that evils, pains, and sadness are natural product of this world, and these evils are not a part of Allah’s (S.W.T) creations. Moreover, the changes are part of the existence of the universe and humans, and these calamities cannot be used as an excuse for not believing in God or justify believing in Anti-natalism.